Privacy-preserving knowledge graph merging - Rajendran, Reenashini (Nanyang Technological University, 2022)
Knowledge Graphs (KG) empower the creation of intelligent systems that can integrate large amounts of data to generate meaningful insights that remain hidden in traditional databases (e.g. Relational databases). Recognizing the robustness of knowledge graphs, big tech companies have spearheaded the adoption of knowledge graphs for data analytics and management, search engines, intelligent agents, and many other applications. In recent years, an increasing number of organisations from all stripes of industries are trying to adopt knowledge graphs to gain a competitive edge. However, the benefits of KGs are limited by data silos within organisations. Organisations often segregate their data into silos due to their security policies. This hinders the formation of a unified KG that is rich and meaningful to the organisation.